2009
DOI: 10.1002/macp.200900327
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Crystallization Kinetics of in situ Prepared Poly(propylene terephthalate)/SiO2 Nanocomposites

Abstract: A series of poly(propylene terephthalate)/silica nanocomposites containing 0.5, 2, 3.5, and 5 wt.‐% SiO2 were prepared by application of the in situ method. The nanocomposites with 3.5 and 5 wt.‐% SiO2 showed an insoluble content because of branching or cross‐linking of the macromolecules, as a result of reaction with the surface hydroxyl groups of silica nanoparticles. Wide‐angle X‐ray diffraction (WAXD) patterns of the composites were identical with that of neat poly(propylene terephthalate) (PPT). Crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…For the estimation of the nucleation activity of foreign substrates in a polymer melt using data from non-isothermal crystallization, Dobreva et al [36] suggested a simple method. This method has also been also used for other cases of nanocomposites [37,38].…”
Section: Nucleation Activity Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the estimation of the nucleation activity of foreign substrates in a polymer melt using data from non-isothermal crystallization, Dobreva et al [36] suggested a simple method. This method has also been also used for other cases of nanocomposites [37,38].…”
Section: Nucleation Activity Of Nanoparticlesmentioning
confidence: 99%
“…The method of Dobreva et al [36], properly modified for cold crystallization, was also used to estimate the nucleation activity of the silica nanoparticles in case of non-isothermal cold-crystallization of the nanocomposites compared to neat PESu. In this case, the nucleation activity (4) was estimated from Equations (7), (9) and (10), but in place of DT the following assumption was made: since it is a cold crystallization, the temperature difference of the crystallization temperature from the glass transition temperature is the determining parameter and not the difference from the equilibrium melting point of the polymer.…”
Section: Nucleation Activity Of Nanoparticlesmentioning
confidence: 99%
“…In this work the method of moments [55][56][57][58][59] has been chosen to model the molecular weight developments during polymerization. The respective model equations for a batch isothermal reactor are summarized in Table 2.…”
Section: Diffusion Controlled Limitations For Termination Reactionsmentioning
confidence: 99%
“…in a batch system commonly results in an infinite system of differential equations with respect to the chain length. [25] In the present study, the method of moments was employed to recast the infinite system of dynamic molar species balance equations into a low-order system of differential equations for the leading moments of the ''live'' and ''dead'' numberchain-length distributions (NCLDs) that can be easily solved. The method of moments is based on the statistical representation of the average molecular properties of the polymer chains in terms of the leading moments of the NCLDs of the ''live'' and ''dead'' polymer chains.…”
Section: Polymerization Rate Functionsmentioning
confidence: 99%